THE ROLE OF FINANCIAL LITERACY AND RELIGIOSITY ON STUDENT SAVING INTEREST - Muammar Al Hamidhi; Achmad Zaki (I-Finance Journal, 2024)
This study aims to investigate the effect of financial literacy and religiosity on students' interest in saving. The population of this study were 126 students of the Management Study Program at Nahdatul Ulama University. The sample was taken based on the criteria, namely those who had obtained courses related to financial literacy so that a sample of 45 people was obtained. The analysis technique uses multiple regression with hypothesis testing, namely the t test and F test. The t test results show that the level of financial literacy partially has a significant effect on students' interest in saving. Religiosity partially has a significant effect on students' interest in saving. The results of the F test show that simultaneously the level of financial literacy and religiosity has a significant effect on students' interest in saving. The conclusion is that both partially and simultaneously the level of financial literacy and religiosity has a significant effect on students' interest in saving.